MASLAHAH DALAM PELEGALAN TAS’IR MENURUT IBNU QAYYIM AL-JAUZIYYAH - Ainiah Abdullah Ainiah (IAIN Langsa, 2019)
Maslahah became one of the approaches in ijtihad and took vital role in the Islamic jurisprudence. In each sharia it is ensured that a law must contain a maslahah to attain goodness and to avoid harms. This research identifies the Maslahah in practicing tas’ir in Ibn Qayyim Al-Jauziyyah’s view. This is a qualitative research with the study of figure’s literatute as objects of study that is Ath-Thuruq al-Hukmiyyah. In this research maslahahs are found in tas'ir policy, they are jalbul mashalih and daf’ul mafasid. Among the practices is the determination of Qimah al-Mitsl, the normal and reasonable price when the inequality occurs in the market. In terms of Mashalih Jalbul, tas'ir is aimed at keeping the public interest in both the world and the hereafter. While in terms of Daf'ul mafasid, Tas'ir is aimed at preventing the wrongdoing, avoiding interference of other parties’ property improperly, and preventing riots and damage on the earth.